A latent class analysis of brand prestige - Prince, Melvin; Davies, Mark (Model Assisted Statistics and Applications, 2009)
Core constructs are necessary as a basis for scale development in brand prestige research. This study examines the theoretical rationale for two such concepts - brand excellence and status conferral - and uses latent class scaling in an empirical test as to whether they are both important independent dimensions of prestige brands. Based on the analysis, these concepts are shown to be consistently present for two brands in two diverse product categories. The research calls into question earlier work on the measurement of brand prestige that was premised on a one-dimensional concept of prestige. Further studies are needed to explore the dimensionality and substantive structure of the brand prestige concept, to confirm or disconfirm findings from this research. © 2009 IOS Press. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/038-210-773-767-532 tex.type: [object Object]
Keywords: Brand excellence; Latent class scaling; Prestige brand; Status conferral; dept.mkt

The animal within - Prince, Melvin; Davies, Mark (Business Strategy Review, 2004)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-656-633-545-989 tex.type: [object Object]
Keywords: dept.mkt

Qualitative analysis and the construction of causal models - Prince, Melvin; Manolis, Chris; Tratner, Susan (Qualitative Market Research: An International Journal, 2009)
Purpose: The purpose of this paper is to provide a methodology by which qualitative analyses serve as rich source materials for discovery of theoretically cogent interrelations between latent variables. Design/methodology/approach: In an illustrative case, qualitative data are collected from US franchisee managers from a single branded franchise of automotive repair outlets. Qualitative analysis of franchisee experiences and attitudes is critical for construction of a causal model used to predict conflict intensity between franchisee managers and franchisors. Findings: The model is based on franchisees' normative expectations for resource allocation within the franchise; and their perceptions of franchisor normative violations, which are determinative of grievances, distrust, and hostility. This theoretical orientation serves to generate a system of interrelated empirically testable propositions. Research limitations/implications: In principle, the primary limitation of using qualitative analysis for the construction of causal models is the fruitfulness of the theoretical orientation shared by the qualitative analyst and the causal modeler. Practical implications: The methodological approach advanced in this paper advances qualitative research and causal modeling beyond the individual contributions. Qualitative analysis infuses variables and process imagery into causal modeling. In turn, causal modeling elaborates the qualitative analysis and makes explicit logical connections between variables. Originality/value: This paper advances a methodology by which qualitative analysis and causal model construction may be usefully integrated. Theory-based qualitative analysis may be formalized to map latent concepts and their interrelations. Further, operational measures of these concepts may be adduced from the analysis of textual data. © Emerald Group Publishing Limited.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-869-015-006-521 tex.type: [object Object]
Keywords: Modelling; Qualitative methods; dept.mkt

A model of job performance, job satisfaction, and life satisfaction among sales and sales support employees at a pharmaceutical company - Prince, Melvin; Engle, Robert L; Laird, Kenneth R (Journal of Pharmaceutical Marketing & Management, 2003)
This study investigates the influence of role conflict, role ambiguity, and role strain on job performance, job satisfaction, and life satisfaction among field sales and company sales support employees in a single pharmaceutical company. Because this study is based on data from a single company, these results may not necessarily be generalized to all companies in the industry. In the present research, a path model of the process reveals important variations in response to role conflict, role ambiguity, and role strain between the two classes of employees. For both classes, the influence of decreased role ambiguity is generally positive for measured outcomes. However, reductions in role conflict, while lessening role strain, are likely to result in lower job performance for field sales employees. Decreases in role strain, while improving life satisfaction, may lead to lower job satisfaction for sales support employees. © 2003, Informa UK Ltd All rights reserved: reproduction in whole or part not permitted. All rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-485-139-151-393 tex.type: [object Object]
Keywords: Job performance; dept.mkt; job satisfaction; life satisfaction; pharmaceutical sales; role strain